Saber sheath trachea in chronic obstructive pulmonary disease patients - Verma, Lokesh; Borana, Hemant; Desai, Govind; Tak, Sanidhaya (International Journal of Advances in Medicine, 2019)
Saber sheath trachea is defined as an anteroposterior (sagittal) diameter of intrathoracic trachea exceeding to lateral (coronal) by a ratio of 2:1 as measured at the site 1 cm above the aortic arch and the extra thoracic trachea being normal. It is most commonly seen in males and is considered to be a diagnostic sign of Chronic obstructive pulmonary disease.